STRATEGI PENGEMBANGAN USAHATANI KEDELAI ORGANIK DI KECAMATAN SONDER KABUPATEN MINAHASA (Organic Soybean Business Development Strategy in Sonder Sub District, Minahasa Regency) - Flyndo Hiskia Gerung; Lyndon R. J. Pangemanan; Juliana R. Mandei (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
The objective of this research was to analyze the strategy for developing organic soybean farming in Sonder District, Minahasa Regency. This research was carried out for 2 months, from April to May 2022. The place of this research was carried out in Sonder District, Minahasa Regency. This study uses primary data and secondary data. Primary data were obtained from direct observation and interviews with respondents based on a list of questions. Secondary data were collected and obtained from agencies related to this research. The sampling method used purposive sampling method, namely by taking samples intentionally as many as 5 people consisting of the head of the farmer group, consultant, BPP coordinator, field extension workers and the government. The informants were chosen because they were considered to have a better understanding of the existing problems in order to determine the soybean development strategy in Sonder District. Descriptive data analysis and, using analysis of Strengths, Weaknesses, Opportunities and Threats (SWOT). Based on the results of the study it can be concluded that the alternative Strength Opportunity (SO) strategy is as follows: increasing production by utilizing unused land by using grobogan variety soybeans according to factory demand, rearranging planning regarding the suitability of seed assistance and seed needs, with the existence of land certificates organic matter from ICERT so that the requirements for organic land meet the requirements for land use and support the development of organic soybeans in Sonder Sub District, and utilize organic fertilizer raw materials which are always available so as to support increased soybean production.